Rapid inclusivity assessment for digital agriculture services - Steinke, Jonathan; Schumann, Charlotte (Bioversity International and the International Center for Tropical Agriculture, 2022)
Digital tools and services are transforming smallholder agriculture, but many farmers are excluded from the benefits of the fast-moving digital revolution. Limited literacy, lack of investment capacity, or poor mobile infrastructure create digital exclusion. Because overall, women are more affected by such forms of exclusion than men, new digital services risk exacerbating gender disparities. Using gender-aware design methods, researchers can generate digital solutions that minimize or mitigate gendered exclusion. This simple tool for ‘Rapid Inclusivity Assessments’ helps researchers, designers and developers identify risks of digital exclusion in their specific project context. The tool then supports them in generating ideas towards improving the inclusivity of their digital agriculture service. The guide helps users carry out a half-day workshop (virtual or on-site) in which the entire design team tests their digital service idea against the potential limitations faced by women farmers on the ground.